Prospecção de substâncias com potencial anticâncer em microrganismos associados ao zoantídeo Protopalythoa variabilis (cnidaria, anthozoa) - Sahm, Bianca Del Bianco (2014)
Natural products exhibit a fundamental role in the discovery of new medicines. Marine natural products possess a huge chemical and pharmacological potential to yield new leads. Previous results support the promising chemical and pharmacological potential of the zoanthid Protopalythoa variabilis from the coast of Ceara State. On the other hand, strong evidences have indicated that associated microorganisms are the producers of the elaborate arsenal of secondary metabolites isolated from marine invertebrates. Then this study aimed to investigate the biomedical potential of associated microbiota to P. variabilis. The efforts to isolate associated bacteria yielded 10 different strains, and 3 of them showed typical actinomycete morphology. Here 2 of these actinomcetes had their anticancer potential studied. The strain BRA-035 belongs to the genus Streptomyces. BRA-035 culture using A1 broth yielded an acetate extract with potent cytotoxicity against a prostatic carcinoma cell line (PC-3/M), with inhibitory concetrantion mean (IC50) value in pg/mL. The bioguided fractionation led to the isolation of glucopiericidin A, piericidin D and piericidin A, and the later showed high antiprolifetative activity against ovarian cancer (OVCAR-8), colon cancer (HCT-116) and PC-3/M with IC50 values ranging from pico to fentomolar. Although Piericidin A has been widely studied, this might be the first report of cytotoxic activity against the lineages tested in this work, as well as the magnitude of its potency. Another strain selected for this study, BRA-060, was identified as belong to the genus Streptomyces also. The fermentation was optimized in marine broth to produce an acetate extract highly cytotoxic against a leukemia cell line (HL-60). The bioguided fractionation of these extracts yielded three diketopiperazines: cyclo (L-Try-trans-L-Pro); cyclo (L-Phe-cis-4-OH-D-Pro) and cyclo (L-Phe-trans-4-OH-D-Pro). The diketopiperazines isolated showed potent cytotoxic activity against glioblastoma (SF-295), ovarian cancer (OVCAR-8), HCT-116, HL-60 and another leukemia (K-562) The IC50 values ranging from nanomolar and micromolar. Althought their structures have already been described in the literature, there was no previous report of their cytotoxic acitivities. Altogether, these results emphasize the value of microbiota associated with the zoanthid P. variabilis, found on the coast of Ceará State, as a source of active compounds.